Kontestasi Politik Hukum Nasional dan Islam: Analisis Kritis atas Pembubaran Ormas dan Regulasi Ideologi di Indonesia - Mahfud (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Agama Islam Miftahul Ula (STAIM) Kabupaten Nganjuk, Indonesia., 2025)
The Contestation of National Legal Politics and Islamic Law in the Context of the Dissolution of Civil Society Organizations, Ideological Regulation, and Strategic Policies in Indonesia. The main focus is directed toward the revocation of the legal status of Hizbut Tahrir Indonesia (HTI), the discourse on the Pancasila Ideology Guidelines Bill (RUU HIP), and the Omnibus Law policy. This study employs a qualitative research method with a normative legal approach, examining statutory regulations, academic literature, and Islamic legal doctrines. The analysis is carried out through legislative, conceptual, historical, and comparative approaches to identify both the convergences and divergences between national legal politics and Islamic legal politics. The findings reveal that the dissolution of HTI can be understood as a form of national legal politics aimed at safeguarding the sovereignty of the Pancasila ideology, while simultaneously aligning with the principle of Maslahah Mursalah in Islamic law to prevent potential harm. The discourse on RUU HIP reflects the legislature’s effort to strengthen the national ideology but risks generating controversy due to the potential politicization of Pancasila. Meanwhile, the Omnibus Law underscores the orientation of national law toward economic efficiency, though it has faced criticism for allegedly weakening social and environmental protections. Thus, the contestation between national legal politics and Islamic legal politics highlights the importance of integrating the legitimacy of positive law with the principle of public welfare (maslahah) in formulating regulations